Head to Toe Psychiatry: The Lady Who Limped in front of a Psychiatrist - Emmanuel Stip; Hind Mohammed Ahmed; Syed Fahad Javaid; Leena Amiri (Case Reports in Psychiatry)
Physical examination is a core component of any assessment done by a physician. Despite that, a physical examination is not always a top priority in many patients with psychiatric illnesses. We present the case of a woman with a prior diagnosis of a delusional disorder with overinvested religious beliefs. The patient had been stable on treatment for many years and only recently presented with a physical complaint, and manifestation assumed to be due to the nature of her psychiatric illness and, hence, overlooked by many physicians before being examined by her last psychiatrist. This resulted in a significant mobility problem for the patient. The patient showed partial insight, linking her pain to a “message from God.” Despite the delusional context, the psychiatrist was allowed to examine her feet and discovered significant neglect and poor foot hygiene. This case emphasizes the importance of conducting thorough physical examinations in psychiatric settings. Moreover, it presents an example of situations preventing psychiatric patients from being examined despite displaying obvious physical signs.